The impact of mobilization training time during the first postoperative week on the length of hospital stay in postoperative patients admitted to an intensive care unit - Yusuke Ozaki; Yuji Kono; Ayato Shinohara; Tomoyuki Nakamura; Takuma Ishihara; Osamu Nishida; Yohei Otaka (Journal of Rehabilitation Medicine)
Objective: To determine the impact of mobilization training time during the first postoperative week on the length of hospital stay for postoperative patients admitted to an intensive care unit.